Kelembagaan Klaster Peternakan Sapi Perah di Kabupaten Malang - Sutawi Sutawi; Indah Prihartini; Asmah Hidayati; Daroe Iswatiningsih (Jurnal Pengabdian Pada Masyarakat, 2020)
INSTITUTIONAL FOR DAIRY CATTLE FARMING CLUSTER IN MALANG REGENCY. Institutional farmers become one of the ideal facilities to empower dairy farmers. The strategy considered effective in developing dairy cattle agribusiness is through a cluster-based regional institutional approach. This study aims to identify the institutional profile of the dairy farming cluster cluster in Malang Regency. The study was conducted in November 2019 with survey methods in Ngantang and Kasembon Subdistricts which are the centers of dairy cattle population in Malang Regency. Research respondents were dairy farmers, administrators of the Farmers Group and the Association of Farmers Groups, KUB, KUD, and institutions related to dairy cattle agribusiness in Ngantang and Kasembon Districts. The institution of dairy farming is an agribusiness industry cluster consisting of five subsystems, namely: (1) upstream institutions, namely breeding companies, feed and drug companies, equipment industries, and others; (2) farming institutions, namely Farmers Group and the Association of Farmers Groups; (3) downstream institutions, namely dairy cooperatives, KUB and KUD; and (4) marketing institutions managed by cooperatives, namely farmers, primary cooperatives, secondary cooperatives, milk processing industry (MPI), wholesalers, retailers and consumers, and non-cooperative channels, namely MPI, distributors, exporters.